Analisis Inovasi Pembelajaran PKN di MI/SD - Abdulgani Jamora Nasution; Efrina Mora; Laila Iklimah Panjaitan; Lutfiah Hanny (EduInovasi: Journal of Basic Educational Studies, 2023)
Citizenship education given to elementary schools is currently based on the current 2013 curriculum. The nomenclature of subjects developed is Pancasila Education and Citizenship. Minister of Education and Culture No. 37 of 2018 is a change from Permendikbud No 24 of 2016 which contains content (core competencies and basic competencies) developed in primary and secondary education. This study used the literature review research method, in which literature review research is the result of analyzing various conceptual information as well as qualitative and quantitative data from various previously published scientific articles. This research resulted that PPKN Learning Innovation in Era 4.0 can be interpreted as a new effort in the learning process by using various approaches, models or methods, facilities, and a learning atmosphere that supports the achievement of learning objectives. Keywords: Innovation, Learning, PKN